DAYA SAING KARET ALAM SUMATERA SELATAN DALAM PERDAGANGAN INTERNASIONAL - Sri Hertina; Khoirun Nisyak; Nur Aslamiah Supli (Indonesian Journal of International Relations, 2021)
Rubber is the leading commodity in South Sumatra which provides the largest income in the non-oil and gas sector. South Sumatra itself is an area that has the largest rubber production and plantations in Indonesia and can even compete with other rubber-producing countries in the international market. However, in its development, South Sumatra's rubber commodity faces various obstacles to compete in international trade. The purpose of this study was to examine how the competitiveness of South Sumatra's natural rubber commodities in international trade. The concept of competitiveness and the theory of competitive advantage is used to describe the research results. The method used in this study is descriptive explanatory, data collection was obtained by interviewing the South Sumatra Province Plantation Service and GAPKINDO of South Sumatra, as well as through the results of a literature study. The findings of this study are seen through 4 determinants of competitive advantage, factor conditions, demand condition, related and supporting Industries, then firm strategy, structure, and rivalry. As well as additional factors, governance. Production of rubber plantations in South Sumatra has decreased. Rubber demand also declined based on data on the volume of rubber exports. South Sumatra's downstream industry has not yet developed. Then the strategy applied is less than optimal and the role of the Government of South Sumatra is lacking. So it can be concluded that the competitiveness of South Sumatran rubber commodities in international trade is low.